The Influence of Price, Facilities and Location on Visiting Decisions (Study on Caffe Point Zero Tanah Tinggi, South Ternate City District) - Liandini Asri; Yolanda Mohungo; Irfandi Buamonabot; Laela L (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2024)
There are various factors that can influence the decision to visit, such as price, facilities and location. However, research results reveal inconsistent results, so this research aims to reexamine factors such as price, facilities and location that can influence visiting decisions, especially in the context of cafes. This research was conducted at the zero-point cafe, Tanah Tinggi subdistrict, Ternate City. The population in this study was all visitors to the zero-point cafe, however the sample only involved consumers who had visited at least two, totaling 126 respondents. Data collection uses surveys with questionnaires. Furthermore, hypothesis testing in this research uses PLS – SEM. The test results revealed that of the three hypotheses proposed, only the hypothesis that tested the influence between price and visiting decisions was accepted in the cafe context in this research. Furthermore, in the final section there will be a discussion of the findings and conclusions.